Genome-wide DNA-methylation landscape defines specialization of regulatory T cells in tissues - Delacher, Michael; Imbusch, Charles D.; Weichenhan, Dieter; Breiling, Achim; Hotz-Wagenblatt, Agnes; Traeger, Ulrike; Hofer, Ann-Cathrin; Kaegebein, Danny; Wang, Qi; Frauhammer, Felix; Mallm, Jan-Philipp; Bauer, Katharina; et al. (Nature Immunology, 2017)
Regulatory T cells (Treg cells) perform two distinct functions: they maintain self-tolerance, and they support organ homeostasis by differentiating into specialized tissue Treg cells. We found that epigenetic modifications defined the molecular characteristics of tissue Treg cells. Tagmentation-based whole-genome bisulfite sequencing revealed more than 11,000 regions that were methylated differentially in pairwise comparisons of tissue Treg cell populations and lymphoid T cells. Similarities in the epigenetic landscape led to the identification of a common tissue Treg cell population that was present in many organs and was characterized by gain and loss of DNA methylation that included many gene sites associated with the TH2 subset of helper T cells, such as the gene encoding cytokine IL-33 receptor ST2, as well as the production of tissue-regenerative factors. Furthermore, the ST2-expressing population was dependent on the transcriptional regulator BATF and could be expanded by IL-33. Thus, tissue Treg cells integrate multiple waves of epigenetic reprogramming that define their tissue-restricted specialization.
CRIS-Team Scopus Importer:2023-03-23